Data Analysis of COVID-19 Exploration on the 'Peduli-lindungi' Application in Indonesia - Passarella, Rossi; Exaudi, Kemahyanto; Oktariani, Gulfi; Salassa, Xosya (Iraqi Journal of Science, 2025)
The peduli-lindungi (Care-Protect) application is an official application used by the Indonesian government to monitor crowds of people who are active in closed and public spaces. The purpose of this application is to facilitate actions that can be taken by the government to prevent the spread of COVID-19. One of the actions is user tracing. In this study, an analysis was carried out on data originating from the Peduli-lindungi Application, which is confidential. Some of the data fields used are still protected by the government. To get accurate data analysis results, preprocessing techniques are carried out on Peduli-lindungi data to produce new datasets as observational data material. The results obtained show that 4073 data points were successfully observed based on the population identification number (NIK) or that there was a reduction in the number of observation data points by 2.83% from the Peduli-lindungi source data. The exploratory data analysis (EDA) method and data visualization techniques using Scimago Graphica and Orange Data Mining were successfully applied to this study. The analysis results obtained show that as many as 13% of the number of people based on NIK do not comply with government regulations on traveling or entering public places, as indicated by the color status in the Peduli-lindungi application, namely red and black. As many as 60% of them do their activities by entering shopping centers, namely malls. Based on the results of the observations and data analysis that have been carried out in this study, it can be concluded that the MALL location is a cluster that must be the center of attention for the government.